2013
DOI: 10.1007/s12192-013-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

In MMTV-Her-2/neu transgenic mammary tumors the absence of caveolin-1−/− alters PTEN and NHERF1 but not β-catenin expression

Abstract: In a recent study, we have shown that in mammary tumors from mice lacking the Cav-1 gene, there are alterations in specific heat shock proteins as well as in tumor development. With this in mind, we have now investigated other proteins in the same mammary mouse tumor model (Her-2/neu expressing mammary tumors from Cav-1 wild type and Cav-1 null mice), to further comprehend the complex tumor-stroma mechanisms involved in regulating stress responses during tumor development. In this tumor model the cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a previous study [31] the authors stated that b-catenin signaling is a critical event in HER2-mediated mammary tumour progression using a mouse tumor model where b-catenin was clearly noted in the nucleus; however, in human breast cancer samples the same authors showed b-catenin localization in the cytoplasm, not in the nucleus [31]. This is an important point, in some HER2 mouse models showing nuclear b-catenin, the up-regulation of direct b-catenin transcriptional targets (like Cyclin D1, Sox9, and c-Myc) may explain the aggressive behaviour of the mammary tumors [10,31], but this is not seen in another HER2 mouse model [11][12][13], and certainly seems not to reflect the situation in human breast cancers. More studies are needed to know why in breast cancers b-catenin is rarely observed in the nuclear compartment.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous study [31] the authors stated that b-catenin signaling is a critical event in HER2-mediated mammary tumour progression using a mouse tumor model where b-catenin was clearly noted in the nucleus; however, in human breast cancer samples the same authors showed b-catenin localization in the cytoplasm, not in the nucleus [31]. This is an important point, in some HER2 mouse models showing nuclear b-catenin, the up-regulation of direct b-catenin transcriptional targets (like Cyclin D1, Sox9, and c-Myc) may explain the aggressive behaviour of the mammary tumors [10,31], but this is not seen in another HER2 mouse model [11][12][13], and certainly seems not to reflect the situation in human breast cancers. More studies are needed to know why in breast cancers b-catenin is rarely observed in the nuclear compartment.…”
Section: Resultsmentioning
confidence: 94%
“…We have previously used a MMTV-c-neu transgenic mouse tumor model to evaluate proteins related with metastasis formation [11,12]. We found in breast tumors driven by specific expression of HER2 a striking co-expression of bcatenin and HER2 in the tumor cells, the absence of caveolin-1 in the tumor stroma had no effect on expression or localization of b-catenin and HER2, both proteins always appeared co-expressed at the cell surface during tumor development and progression [13]. This is in contrast to what has been reported in human breast tumor tissues where most of the times b-catenin was expressed in the cytoplasm, and where the disease-free survival (DFS) and overall survival (OS) were significantly shorter for patients expressing b-catenin in the cytoplasm only, not at the plasma membrane [1].…”
Section: Introductionmentioning
confidence: 99%